Cultures of desistance: rehabilitation, reintegration and ethnic minorities - Calverley, Adam (Routledge, 2013)
In contrast to the widespread focus on ethnicity in relation to engagement in offending, the question of whether or not processes associated with desistance ' that is the cessation and curtailment of offending behavior ' vary by ethnicity has received less attention. This is despite known ethnic differences in factors identified as affecting disengagement from offending, such as employment, place of residence, religious affiliation and family structure, providing good reasons for believing differences would exist